Chemical composition and insecticidal properties of essential oils against diamondback moth (Plutella xylostella L.). (1st October 2020) - Koundal, Rajkesh; Dolma, Shudh Kirti; Chand, Gopi; Agnihotri, Vijai K.; Reddy, S. G. Eswara
Abstract: Seven essential oils viz., Curcuma aromatica, Hedychium spicatum, Mentha piperita, M. spicata, M. longifolia, Cinnamomum camphora, and Cymbopogon flexuosus were evaluated for their insecticidal activities against the larvae of the diamondback moth, Plutella xylostella (L.). Results showed that M. longifolia was most toxic (LC50 =1.06 mg mL −1 ) to second instar larvae of P. xylostella via residual toxicity bioassay followed by C. aromatica (LC50 =1.35 mg mL −1 ) and M. piperita (LC50 =1.37 mg mL −1 ). M. piperita and M. spicata showed promising repellent (RC50 =1.33 mg mL −1 ) and feeding deterrence activity (66.07%) to third instar larvae, respectively.